Are attitudes towards economic risk heritable? Analyses using the Australian twin study of gambling - Anh Tram Le; Paul W. Miller; Wendy S. Slutske; Nicholas G. Martin (Institute for the Study of Labor (IZA), 2010)
This study employs multiple regression models based on DeFries and Fulker (1985), and a large sample of twins, to assess heritability in attitudes towards economic risk, and the extent to which this heritability differs between males and females. Consistent with Cesarini, Dawes, Johannesson, Lichtenstein and Wallace (2009), it is found that attitudes towards risk are moderately heritable, with about 20 percent of the variation in these attitudes across individuals being linked to genetic differences. This value is less than one-half the estimates reported by Zyphur, Narayanan, Arvey and Alexander (2009) and Zhong, Chew, Set, Zhang, Xue, Sham, Ebstein and Israel (2009). While females are more risk averse than males, there is no evidence that heritability in attitudes towards risk differs between males and females. Even though heritability is shown to be important to economic risk taking, the analyses suggest that multivariate studies of the determinants of attitudes towards risk which to not take heritability into consideration still provide reliable estimates of the partial effects of other key variables, such as gender and educational attainment.
Keywords: G00; J01; 330; Risk; heritability; gender; Risikopräferenz; Gentechnik; Geschlecht; Australien